Possible Florida Invader: Green Anaconda - Steve A. Johnson; Monica E. McGarrity (EDIS)
WEC289, a 2-page illustrated fact sheet by Steve Johnson and Monica McGarrity, is part of the Florida Invaders series. It provides key information and illustrations for identifying and reporting sightings of this large, nocturnal predator that is native to tropical South America and is not established in Florida, but escaped or released pets have been encountered in the wild. Published by the UF Department of Wildlife Ecology and Conservation, September 2010.